(untitled) (Medical Forum Monthly, 2020)
Objective: To study the frequency of cardiac anomalies in patients of high and low variety anorectal malformation (ARM) Study Design: Prospective Observational study Place and Duration of Study: This study was conducted at the Inpatient Department of Pediatric Surgery, Nishtar Hospital, Multan and Children Hospital and Institute of Child Health Multan for 06 months from July, 2019 to January, 2020. Materials and Methods: After the approval of ethical committee, parental informed consent was taken from the parents before the commencement of study. All the neonates that presented with absent anus, had undergone Invertogram study and were classified as low or high ARM. Echocardiography was performed in all patients to diagnose cardiac anomalies. Data was collected on a predesigned performa and analyzed statistically on SPSS version 20. Results: Out of 121 patients, 83 (68.6 %) were male patients while 38 (31.4 %) were female patients. Mean age of our study cases was 1.23 ± 0.513 days. Those who belonged to rural areas were 74 (61.2 %) and 47 (38.8 %) belonged to urban areas. Mean gestational age of these children was 38.14 ± 1.29 weeks and 106 (87.6%) had gestational age more than 36 weeks. Regarding mode of delivery, 99 (81.8%) were born vaginally and 22 (18.2%) through cesarean section. Positive family history of anorectal malformations was noted in 9 (7.4%) whereas 89 (73.6%) mothers were illiterate. Low variety ARM was found in 59 (48.8%) cases and high variety ARM in 62 (51.2%) while cardiac anomalies were noted in 40 (33.8%). Conclusion: Very high frequency of cardiac anomalies was noted in our study among neonates presenting with anorectal malformation. Cardiac anomalies were significantly associated with gender, family history of anorectal malformation and high variety of ARM. Such patients can be helped by early diagnosis and timely management to decrease burden of related morbidity and mortality.